(untitled) (Archive of Conferences, 2021)
It is known that the source of electromagnetic waves in the optical range is anythe constituents of a substance are its atoms, ions, or molecules. These particles are externalcan be awakened by the action of an electromagnetic field. He woke upThe lifetime of the atom in the state is 10-8 s. An example of an external effect on an atom in this caseIf the electromagnetic field is not affected, then the characteristic of the awakened state is highthe transition from the energy level to the lower energy level is spontaneous, that is, randomincreases. Spontaneous radiation to the radiation process that results from such a transitionis called.